Identification and Validation of Long Non-Coding RNA LCIIAR as a Biomarker in LUAD - Ren, Wenjun; Yuan, Yixiao; Chen, Xi; Zhai, Haoqing; An, Yin; Tang, Lin; Wang, Juan; Zhang, Dahang; Zhang, Liren; Cheng, Wanli; Wang, Xin; Duan, Lincan; et al. (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related death worldwide. Therapies for lung cancer have relatively poor outcomes, thus further improvements are required. Lung cancer immune cell infiltration associated RNA (LCIIAR) is a long noncoding RNA (lncRNA), which is overexpressed in human cancers. However, the clinical significance and functional role of LCIIAR in lung adenocarcinoma remains unclear. Here, we identified a novel long non-coding RNA (lncRNA, ENSG00000256802), termed LCIIAR (lung cancer immune cell infiltration associated lncRNA), up-regulated in lung cancerous and cell lines. We show that increase LCIIAR expression correlated with poor clinical stage and adverse clinical outcomes in lung adenocarcinoma patients. Furthermore, our results confirmed that LCIIAR could serve as an independent unfavorable prognostic factor in patients with lung adenocarcinoma. GSEA analysis demonstrated that LCIIAR mainly involved in the immune response regulation related signaling pathway. Meanwhile, we uncovered that elevate LCIIAR expression positively correlated with immune infiltration and immune modulator in lung adenocarcinoma. More important, we confirmed that silencing of LCIIAR expression significantly inhibits the cell proliferation, and migration abilities of lung adenocarcinoma. Our findings revealed the critical role of LCIIAR in LUAD progression, which may serve as a prognostic biomarker and novel therapeutic target.